Adding Value to the Applied Sport Management Association - Mike Martinez (Journal of Applied Sports Management, 2022)
Dr. Martinez is the inaugural recipient of the Distinguished Service Award for the Applied Sport Management Association (ASMA). He offers his thoughts on adding value to ASMA to advance the association and sport management.
Keywords: ASMA; conference; value; distinguished service award